Campanula portenschlagianaRoem. et Schult.: Chemical and Antimicrobial Activities. Issue 6 (18th June 2013) - Politeo, Olivera; Skocibusic, Mirjana; Burcul, Franko; Maravic, Ana; Carev, Ivana; Ruscic, Mirko; Milos, Mladen
Abstract The phytochemical profile and the antimicrobial effects of the volatile oil and the aqueous extract of Campanula portenschlagiana, a wild growing plant endemic to Croatia, were described. In the volatile oil, 53 compounds were identified by GC‐FID and GC/MS analyses. Diterpene alcohols constituted the major compound class with labda‐13(16), 14‐dien‐8‐ol as the main compound. The aqueous extract was characterized by the total phenolic content. The antimicrobial potential of the volatile oil and the aqueous extract was evaluated against a diverse range of microorganisms comprising food‐spoilage and food‐borne pathogens. The volatile oil exhibited interesting and promising antimicrobial effects against the tested species, which were generally more pronounced against Gram‐negative bacteria. In addition, the inhibitory effect of this volatile oil was also evaluated against eleven extended‐spectrum β‐lactamase (ESBL)‐producing isolates. The results suggest that the C. portenschlagiana volatile oil might be used as antimicrobial agent against ESBL‐producing isolates and Gram‐negative bacteria.